Pengaruh Pengaruh Pemotongan Bibit dan Konsentrasi Urin Kelinci Terfermentasi Terhadap Pertumbuhan dan Hasil Bawang Daun (Allium fistulosum L.): - - wuryantoro wuryantoro (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2022)
The spring onion plant (Allium fistulosum L.) has the potential to be developed considering the many benefits obtained from this plant, especially for various kinds of cuisine. Therefore, efforts to improve product quality and quantity need to be continued. The use of rabbit urine can help minimize the use of inorganic fertilizers. While cutting techniques will increase heat efficiency. This study aims to determine the effect of the seed length of spring onion seeds and rabbit urine fermentation on the growth of spring onion. This study used a factorial randomized block design consisting of two factors and three replications. The first factor includes cutting the seeds, namely (P1) 10 cm, (P2) 15 cm, and (P3) 20 cm. The second factor was the concentration of rabbit urine fermentation (U1) at 50 ml/l, (U2) at 100 ml/l, and (U3) at 150 ml/l. The results showed that there was an interaction between the dose of rabbit urine fermentation and cutting seeds on the growth of leek plants. The longer the seedling size, the more the response to rabbit urine concentration for leaf vegetative parameters and fresh plant weight. The highest yield was achieved with a seed size of 20 cm with a concentration of fermented rabbit urine of 150 ml/l with an average yield of 39.8 leaves per plant and a fresh weight of 442.52 grams per plant. There is a tendency for seed size to grow which can be stimulated by high urine concentrations, thus allowing the use of urine with higher concentrations and doses